Systems analysis and design in a changing world - Satzinger, John W.; Jackson, Robert B.; Burd, Stephen D. (Course Technology, 2016)
Reflecting the practices, trends, and developments from the field, this title equips you with a solid foundation of the important principles of systems analysis, systems design, project management, and new software development approaches. It teaches both traditional (structured) and object-oriented (OO) approaches to systems analysis and design